2020
DOI: 10.1101/2020.08.21.260216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective dephosphorylation by PP2A-B55 directs the meiosis I - meiosis II transition in oocytes

Abstract: Meiosis is a specialized cell cycle that requires sequential changes to the cell division machinery to facilitate changing functions. To define the mechanisms that enable the oocyte-to-embryo transition, we performed time-course proteomics in sea star oocytes from prophase I through the first embryonic cleavage. Although protein levels are broadly stable, dynamic waves of phosphorylation underlie each meiotic stage. We find that the phosphatase PP2A-B55 is reactivated at the Meiosis I/II transition resulting i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…One possibility is the differential regulation of ERK activity. A recent study using a time-course proteomics approach tested the mechanisms regulating meiosis I-meiosis II transition in synchronized sea star oocytes (Swartz et al, 2021). The authors found that there is a differential regulation of serine and threonine dephosphorylation during the meiosis I-meiosis II transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is the differential regulation of ERK activity. A recent study using a time-course proteomics approach tested the mechanisms regulating meiosis I-meiosis II transition in synchronized sea star oocytes (Swartz et al, 2021). The authors found that there is a differential regulation of serine and threonine dephosphorylation during the meiosis I-meiosis II transition.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that there is a differential regulation of serine and threonine dephosphorylation during the meiosis I-meiosis II transition. Protein phosphatase PP2A-B55 preferentially dephosphorylates threonine residues and thus temporally regulates the activity of its substrates, including CDK and ERK (Swartz et al, 2021). Another possibility is the involvement of other signaling regulators, such as CDK1 or PLK1, which along with ERK, control specific subsets of substrates during the meiosis I-meiosis II transition.…”
Section: Discussionmentioning
confidence: 99%
“…The sAID was fused to the N-terminus of PPP6c to ensure tagging of the three annotated alternative splice isoforms of PPP6c, and to avoid interference with C-terminal methylation. For proteomic and phosphoproteomic analyses of untreated and auxin (IAA) treated cells, three or four biological replicates were generated and analyzed using our established and reproducible workflow (13, 55, 56). For the proteomic study, 40 μg of peptides were removed from the trypsin digest of each condition.…”
Section: Methodsmentioning
confidence: 99%
“…For proteomic and phosphoproteomic analyses of untreated and auxin (IAA) treated cells, three or four biological replicates were generated and analyzed using our established and reproducible workflow (13,55,56). For the proteomic study, 40 μg of peptides were removed from the trypsin digest of each condition.…”
Section: Introductionmentioning
confidence: 99%